Sistem Pengukuran Arus dan Tegangan pada Rangkaian Kombinasi Virtual Lab - Kamarudin Kamarudin; Muhammad Ridwan; Jefri Saputra; Kemas Muhammad Aby (JURNAL INTEGRASI, 2022)
The COVID-19 pandemic has affected the education system in Indonesia. The education system that was originally carried out face-to-face changed to an online system (online). With an online system that seems one-way, many students are unable to absorb the material taught optimally. The purpose of this virtual lab project is to create a practicum trainer with a system of measuring electric current and voltage on a combination circuit that can be measured remotely based on the internet of things. Students can access the practicum trainer through the virtual lab android application to measure the electric current or voltage. Based on the test results of electric current measurement using the INA219 sensor, the highest percentage of error was found when measuring against a resistor of 1200 Ω with an error percentage of 2.5%. While in the voltage measurement using a 25 Volt voltage sensor, the highest percentage of error was found at the time of measurement of the resistor of 500 Ω with an error percentage of 1.43%.